Experimental-numerical characterization of maximum current capability in Si-based surface mounted power devices. (November 2022) - Sitta, Alessandro; Mauromicale, Giuseppe; Corrente, Giovanni; Messina, Angelo Alberto; Rundo, Francesco; Calabretta, Michele; Sequenzia, Gaetano
Abstract: This paper proposes an experimental method devoted at characterizing the maximum continuous drain-source current sustainable by a power semiconductor device. This information, strictly related to thermal limit of the package, is being more and more important, especially for automotive applications, where the robustness must be assured, in terms of reliability. More specifically, usually it is demanded a high value of current which the device must be handled. The test vehicle used in this work is the low-voltage LFPAK package, based on a silicon MOSFET. Moreover, a finite element based model is developed in order to numerically reproduce the experiment: in this way, it is possible to study the system in a more detailed manner, and changes in device's and cooling system's designs can be quickly evaluated.